Anthropocene Effects on Marine Biodiversity (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2024)
The Anthropocene epoch is characterised by an unprecedented acceleration of anthropogenic pressures on marine ecosystems, including ocean warming, acidification, deoxygenation, pollution, overexploitation, and habitat destruction. Collectively, these stressors are reshaping marine biodiversity across all taxonomic levels and oceanic realms, threatening the functional integrity of ecosystems that sustain more than three billion people. This study synthesised long-term monitoring data from 124 marine sites distributed across six oceanic regions -- the North Atlantic, South Atlantic, North Pacific, South Pacific, Indian Ocean, and Arctic -- spanning 1980 to 2023 to quantify multi-decadal trends in species richness, community composition, and functional diversity. Sea surface temperature (SST) increased by a mean of 0.62 +- 0.18 degrees C per decade across all sites, with Arctic warming exceeding 1.41 +- 0.31 degrees C per decade. Species richness declined significantly in tropical reef systems (mean loss = 27.4%, 95% CI: 21.8-33.1%) and polar regions (mean loss = 19.8%) over the study period, while temperate zones showed modest richness gains (+8.3%) attributed to poleward range expansions of warm-affinity species. Functional diversity declined more steeply than taxonomic richness in all regions (functional dispersion loss: 34.2% in coral reefs, 22.6% in polar systems), signalling disproportionate erosion of ecological roles. Ocean acidification (pH decline: -0.14 +- 0.03 units since 1980) was the strongest predictor of calcifier community collapse (R2 = 0.71, p < 0.001). These findings highlight the urgent need for integrated ocean governance frameworks that address multiple stressors simultaneously to prevent irreversible loss of marine biodiversity.